2020
DOI: 10.21608/eajbsf.2020.124238
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Ten Native Edible and Essential Plant Oils Against the Granary Weevil, Sitophilus granarius L. (Coleoptera: Curculionidae)

Abstract: The comparative toxicity of ten selected native essential and edible oils was assessed against S. granarius. The oils used are black seed oil (Nigella sativa), Sesame oil (Sesamum indicum), olive oil (Olea europaea), Peppermint oil (Mentha piperita), Basil Oil (Ocimum basilicum), orange oil (Citrus sinensis), Rosemary oil (Rosmarinus officinalis), Clove oil (Dianthus caryophyllus), Garlic oil (Allium sativum), and Cinnamon oil (Cinnamomum zeylanicum). Different concentrations of oils were mixed with wheat grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…At the opposite, Zohry et al [50] tested toxicity of 10 essential oils on S. granarius by exposure to treated wheat in a protocol close to that of this study. Garlic oil was identified as the most toxic one with a concentration of oil per grams of grain similar to ours.…”
Section: Insecticidal Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…At the opposite, Zohry et al [50] tested toxicity of 10 essential oils on S. granarius by exposure to treated wheat in a protocol close to that of this study. Garlic oil was identified as the most toxic one with a concentration of oil per grams of grain similar to ours.…”
Section: Insecticidal Potentialmentioning
confidence: 99%
“…In addition, most essential oils have low mammalian toxicity in comparison with synthetic insecticides and are considered as eco-friendly [18]. For instance, Stroh et al [19] showed that eugenol was 1500 times less toxic than pyrethrum and 15,000 times less toxic than the organophosphate azinphosmethyl for juvenile rainbow trout based on 96 h-LC 50 values.…”
Section: Introductionmentioning
confidence: 99%